Interactive Effect Of Different Nitrogen Levels And Seed Rates On Yield And Yield Attributes Of Fodder Maize (Zea Mays L.) Under Temperate Conditions Of Kashmir (Applied Biological Research, 2012)
Two year field studies were conducted at Experimental Farm, SKUAST Kashmir to evaluate the effect of 60, 90 and 120 kg N ha-1on fodder  maize sown at seeding rate of 40, 60 and 80 kg ha-1. Application of 120 kg N ha-1significantly increased green and dry fodder yields of maize due to  increase in all yield components studied viz., plant height, leaf area index,  dry matter production and stem diameter. Seed rate of 60 and 80 kg ha-1,  being at par, significantly increased plant height and dry matter over 40  kg seed rate ha-1, whereas, leaf area index recorded significantly higher  values up to 80 kg seed rate ha-1. Stem diameter recorded significantly  lower values with increasing seed rates but green and dry fodder-yield  values were realized statistically higher up to 80 and 60 kg seed rate ha-1,  respectively. Fodder maize sown at seed rate of 80 kg ha-1and receiving  120 kg N ha-1seems to be the best combination in getting maximum  green, succulent and palatable fodder under temperate conditions of  Kashmir.
Keywords: Fodder maize; interaction effect; nitrogen; seed rate; temperate; yield attributes